Learning English as a Second Language: Bangladeshi English-major Learners within intra-cultural Power Relationship - Fatema , Kaniz (EAST WEST JOURNAL OF HUMANITIES, 2017)
Deficiencies in English-major learners’ academic participation lead to question whether intra-cultural power relationship is responsible for learning English as a second language. Here different kinds of influences within an English L2 society like Bangladesh have been investigated which was previously analysed by researchers from inter-cultural perspective. This paper aims at explaining the possible connection of power relations and influence of society by analysing the position of English language among Bangladeshi English-major learners as a program of higher education and its interrelation with the idea of knowledge. This process will show how an individual is bound to think about English language positively in the process of their growing up within intra-cultural power relationship. As learners are interviewed individually to express and share their views and experiences, classroom practitioners for tertiary level learners will get an internal reinforcement of learners in learning English as second language, and, as a part of reflective practice, they will be able to create situations for increasing learners’ academic participation.